2023
DOI: 10.1029/2022sw003213
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ionospheric Fluctuations Over the Circum‐Pacific Regions Following the January 2022 Tonga Volcanic Eruption

Wang Li,
Haoze Zhu,
Jiandi Feng
et al.

Abstract: The Hunga Tonga‐Hunga Ha'apai volcanic eruption on 15 January 2022 had a significant impact on the ionosphere‐thermosphere system, resulting in large‐scale ionospheric irregularities with longitudinal and latitudinal asymmetries. Multiple instruments recorded these irregularities, indicating the propagation of a westward wave at an average velocity of 354 ± 8 m/s, which led to plasma irregularities of 0.2 TECu/min. Conversely, an eastward‐propagating wave was detected on the Pacific's east coast, traveling at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The HTHH volcanic eruption occurred during the recovery phase of a moderate geomagnetic storm. Previous studies (Aa et al, 2022;Astafyeva et al, 2022;Li et al, 2023) stated that this geomagnetic storm had minimal impact on TEC. It was found that the peak of the average TIDs was at ∼09:00-10:00 UT or ∼300 min after eruption with ∼24.8 TECU.…”
Section: 1029/2023ja031806mentioning
confidence: 82%
See 1 more Smart Citation
“…The HTHH volcanic eruption occurred during the recovery phase of a moderate geomagnetic storm. Previous studies (Aa et al, 2022;Astafyeva et al, 2022;Li et al, 2023) stated that this geomagnetic storm had minimal impact on TEC. It was found that the peak of the average TIDs was at ∼09:00-10:00 UT or ∼300 min after eruption with ∼24.8 TECU.…”
Section: 1029/2023ja031806mentioning
confidence: 82%
“…During the event, disturbance on the electric field is responsible for generating the westward equatorial electrojet (EEJ) (Zhang et al, 2021(Zhang et al, , 2022b. Previous research (Aa et al, 2022;Astafyeva et al, 2022;Li et al, 2023) stated that geomagnetic storms might affect TEC, although its effect might be insignificant. In addition, Le et al (2022) stated that the eruption and the geomagnetic storm reversed the neutral wind direction.…”
Section: 1029/2023ja031806mentioning
confidence: 96%
“…Atmospheric pressure disturbances traveled in the form of Lamb waves and surrounded the Earth several times. The volcano eruption can produce effects in the lower atmosphere (varying atmospheric pressure), in the mesosphere and lower thermosphere (MLT) region (modifying neutral winds), as well as in the ionosphere (perturbing the horizontal magnetic field component-H, the vertical plasma drifts, the equatorial electrojet-EEJ, and the virtual height of the ionograms) (Poblet et al 2023;Stober et al 2023;Schnepf et al 2022;Le et al 2022;Sun et al 2022;Li et al 2023;Harding et al 2022;Qiu et al 2023).…”
Section: Introductionmentioning
confidence: 99%